NATURAL ENZYMES AND ALLERGIES (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Enzymes play a crucial role in speeding up chemical reactions in living organisms. Discovered in the late 19th century, these complex proteins are essential for various biological processes. Food allergies are immune responses to specific proteins in food. Common allergens include proteins from eggs, milk, peanuts, tree nuts, and seafood. Allergic reactions can vary from mild to severe and affect different body systems. The prevalence of food allergies is rising, with some estimates suggesting that up to 10% of the population may be affected. The aim of this paper is to investigate the influence of some natural enzymes on allergies. Enzymes used in food processing, like lysozyme in wine or alpha amylase in baked goods, can pose risks for those with sensitivities. Lysozyme, an enzyme that breaks down bacterial cell walls, can cause allergic reactions in some people, particularly those allergic to eggs. Similarly, enzymes like enolases and aldolases, which are involved in energy production, can trigger allergies, especially among those sensitive to fish proteins. Alpha-amylase, an enzyme that breaks down starches, is a well-known allergen, particularly in occupational settings like baking. Arginine kinase, found in seafood and insects, can also cause allergic reactions, which is a concern for people handling these products. Chitinase, which breaks down chitin in insects, and papain from papaya, used in meat tenderizers, can lead to allergies as well. Conclusion: Clearly specifying the natural or synthetic origin of potentially allergenic substances enables the avoidance of allergic reactions and directly contributes to maintaining the health of individuals sensitive to these ingredients.